Verrucous epidermal nevus/Plane warts. - Greco, I.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
Verrucous epidermal nevus is usually differentiated from plane warts thanks to its different history and to different distribution of its lesions. However, sometimes epidermal nevus, especially in the palmar region, can be not evident at birth and warts in their turn can be arranged linearly, making the differential diagnosis between the two disorders more difficult.